ACL Return to Sport Testing: It’s Time to Step up Our Game - Casey Unverzagt; Evan Andreyo; Jeff Tompkins (International Journal of Sports Physical Therapy)
Patients and physicians have long looked to physical therapists to help determine an athlete’s readiness to return to sport (RTS) following anterior cruciate ligament reconstruction (ACLR). This is a complex decision that must take into account biological healing, joint stability, functional performance, and psychological readiness. Considering that the vast majority of medical professionals use time as the sole determinant of an athlete’s readiness, and few are using performance-based criteria, it appears as though our profession is failing to capture the necessary information to make this weighty recommendation. The time is now to take a hard look at current practice patterns with RTS testing and push the envelope forward. The purpose of this clinical commentary is challenge our failing status quo by disseminating a robust model for RTS testing that incorporates temporal and criterion-based factors, as well as intrinsic and extrinsic data.